Religious intolerance: the maximum denial of alterity - Hogemann, Edna; Tavares, Sergio Luis (The Age of Human Rights Journal, 2021)
It analyses aspects of religious intolerance in Brazil, its cause-and-effect relationship with radical proselytism, negative consequences for the exercise of the right to religious freedom and other human rights, some manifestations in the Brazilian multireligious scenario, some potentially effective instruments for prevention intolerance, among which are the practices of alterity. It shows that Brazil, does not present a chaotic picture in terms of intolerance, but has worrying records of persecution, discrimination and acts of violence, for religious reasons, which should serve as a warning for implementation of affirmative actions and public policies regarding the duty of respect and solidarity with others.